STUDENTS’ PROBLEMS IN MASTERING LISTENING SKILL AT THE FIRST SEMESTER OF STUDENTS TOURISM ACADEMY OF ULCLA TARUTUNG - Kanca Silaban (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2021)
This qualitative research was done as an effort to analyze the major factor of the causes of low students’ ability in understanding the English language through listening skill. Whether the low used of media in Tourism Academy of ULCLA as the causes of low Students ability in listening skill. The population research and the sample was the 2020/2021 second grade students of Tourism Academy of ULCLA Tarutung with total 30 students and consists of Hospitality Major. Instrument with used of this research was to use media as audio-lingual to analyze the low students’ ability in studying listening skill. In the collecting data procedures, there are four steps that: Planning, Action, Observation, and Reflection. In the first data, the writer makes the exam material as research material to make simple conversation or with words that are often hear or even frequently used by student their daily lives. But after examination, the result of students’ paper only 25 % from the amount 30 Students. Of these, the writer concludes that the mastery and the skill of students to understanding listening is very low. This cause by the lack of the using of media supporting. After that and show of the value, the writer tries to make the exam about the different sound with the aim so that student knows the difference between native speaker with from their teacher or maybe daily conversation. So the second and the third result of the data at least increase, based the table become 35 % and in this section students acknowledge the different between native speaker pronunciation with subject teachers or the people around them influence practice hearing students. Until fifth test, we can see the percentage of the test of students is very low it means Unsatisfied. the analysis of the causes of low student’s skill in understanding the English language through listening skill are the lack of the using of audiolingual methods and the causes from external and internal of students.